PENGARUH PENDAPATAN ASLI DAERAH, BELANJA MODAL DAN DANA ALOKASI UMUM TERHADAP PERTUBUHAN EKONOMI DI PROVINSI ACEH - Muhammad Havis; Rizki Imam Maulana; Wahyuni Siregar; Puti Andiny; Safuridar Safuridar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Economic growth is an important indicator that reflects the success of regional development. This study aims to analyze the effect of Regional Own-Source Revenue (PAD), Capital Expenditure, and General Allocation Fund (DAU) on economic growth in Aceh Province. The research employs a quantitative approach using time series data from 2009 to 2023, obtained from the Central Bureau of Statistics (BPS). Data were analyzed using multiple linear regression with the Eviews 9 software. The results show that PAD and DAU have a positive and significant effect on economic growth, while Capital Expenditure has a negative and insignificant effect. Simultaneously, the three variables have a significant impact on economic growth with a coefficient of determination (R²) of 78.44%. These findings suggest that local governments need to optimize PAD and manage transfer funds more productively to accelerate sustainable economic growth in Aceh Province